Prevalence of Abnormal Cervical Cytology in Maha Sarakham Province - Nakhapongse, Saowalak; Tonmat, Sakchai (Journal of Health Science of Thailand, 2018)
Cervical cancer was frequently found among Thai women. It can be screened and cured before proceeding to invasive cancer. The purpose of this study was to define the prevalence of abnormal cytology of cervix by pap smear technique in Maha Sarakham province and to study the result of colposcopic examination in Maha Sarakham hospital. All medical records about pap smear and colposcopic reports between January 2006 and December 2007 in this province were reviewed retrospectively. In abnormal cytologic group that proceeded to colposcopic examination, demographic data, colposcopic and histologic report were studied. As a result, abnormal cervical cytology was found in 1,020 of 52,325 specimens, and yielded prevalence rate of 1.95 percent. Which were classified into ASCUS 41.86 percent AGC, HSIL 10.88 percent LSIL 8.24 percent, ASC-H 6.08 percent and SCCA 4.31 percent. Adeno CA and AIS were reported in 1.47 percent and 0.39 percent respectively. There were 753 cases undergoing colposcopic examination. The cytologic detection rate of HSIL, LSIL, AGC, ASCUS and ASC-H were 87.39 percent, 51.47 percent, 12.09 percent, 8.52 percent and 6.45 percent respectively. The detection rate of SCCA, AIS and Adeno CA were all 100 percent. In conclusion, the prevalence of abnormal Pap smear in this study was quite low relative to other studies. All women whom cytologic diagnosed as HSIL and beyond should be refered for colposcopic examination and received treatment early, because of the possible high detection rate of cytopathologic diagnosed as HSIL and its potential progress to invasive cancer.